2013
DOI: 10.1115/1.4025502
|View full text |Cite
|
Sign up to set email alerts
|

Stable Nanofluids for Convective Heat Transfer Applications

Abstract: Nanofluids are stable dispersions of ultrafine or nanoscale metallic, metal oxide, ceramic particles in a given base fluid. It is reported that nanofluids register an extraordinarily high level of thermal conductivity, and thus possess immense potential in improvement of heat transfer and energy efficiency of several industrial applications including vehicular cooling in transportation, nuclear reactors, and microelectronics. The key issues with nanofluids are: (i) a robust, cost-effective and scalable method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Saidur et al, 32 Banerjee, 113 and Chiney et al, 114 as well as others, 115,116 have reported several deficiencies with nanofluid understanding. The synthesis and thermophysical properties of nanofluids are much debated within the literature.…”
Section: Research Gapsmentioning
confidence: 98%
See 1 more Smart Citation
“…Saidur et al, 32 Banerjee, 113 and Chiney et al, 114 as well as others, 115,116 have reported several deficiencies with nanofluid understanding. The synthesis and thermophysical properties of nanofluids are much debated within the literature.…”
Section: Research Gapsmentioning
confidence: 98%
“…The reproducibility of the experiment must be confirmed by conducting the control run after each experimental trial. Note that this is not an inclusive list 114 …”
Section: Research Gapsmentioning
confidence: 99%
“…A correlation equation was proposed for laminar flow-see Table 2. Chiney et al [103] established that the addition of NPs may result in overall HTC improvement up to 54% under laminar flow in a double tube system. It was also found that the degree of intensification of the overall HTC decreased with the increase in the thermal conductivity of the heat transfer wall material.…”
Section: Characteristics Of the Conducted Researchmentioning
confidence: 99%